Petroleum geoscience of the West Africa margin - Sabato Ceraldi, T.; Hodgkinson, R. A.; Backe, G. (The Geological Society, 2017)
The continental margin of West Africa formed as result of the south-to-north rifting of Gondwana and the progressive separation of the South American and African continents. This margin has enjoyed a rich and varied exploration history and, in the 70 years or so since the first significant exploration began in the onshore area, the margin has emerged as a significant hydrocarbon-producing region. The amalgamation of hydrocarbon exploration approaches and imaginative ideas, leveraged with modern technologies, is yielding significant scientific and economic successes. The main objective of this Special Publication is to provide an overview of the advances in our understanding of the crustal structure, tectonic evolution and Mesozoic to Cenozoic stratigraphy of the West Africa margin both onshore and offshore, with a particular focus on the petroleum geology. The papers contained in this Special Publication represent a selection from the 37 abstracts presented at the original conference in March 2014, which covered the entirety of the margin from South Africa to Morocco as well as stratigraphy from the crystalline basement to the most recent strata.
Keywords: Petroleum -- Geology -- Africa, West.; elektronické knihy; electronic books